I write what we like: A textual analysis of Fallist microblogging - Chen, Jon Adam (Centre for Film and Media Studies, 2018)
Fallists belong to a constellation of radical student activist movements that pledge to disturb and reimagine South African society. Rather than restricting themselves to coordinated forms of collective action, Fallists’ advance their “revolution-as-becoming” within a context of everyday resistance (Haynes & Prakash, 1991; Molefe, 2015). In this dissertation, I propose that Fallists form an “emerging networked counterpublic” made up of individual activists that enact everyday forms of resistance on Twitter (Jackson & Foucault Welles, 2016:399). This dissertation explores the use of Twitter by a microblogger who has emerged organically as a “crowdsourced elite” among Fallists (Papacharissi & de Fatima Oliveira, 2012). I contend that this microblogger exemplifies the repertoires of communication and resistance that pervade within Fallist networks on Twitter (Jackson & Foucault Welles, 2016). The microblogger is identified through methods of observation and social network analysis (SNA). “#whitetip,” a Twitter hashtag network that exemplifies Fallist communication and resistance, informs the interpretive content analysis that follows. This analysis is conducted on the tweets that the microblogger broadcast between 1 April and 30 September 2016. Tweets are categorised according to “evaluative frames” that emerged inductively during the course of analysis. I find that “resentment,” “pride and care,” and “play” made up the vast majority of evaluative frames. The microblogger employs the platform in a manner that disturbs dominant understandings of public sphere communication: the microblogger’s tweets are evaluative rather than deliberative, and assert a marginal, embodied subjectivity (Papacharissi, 2014; Warner, 2002).